2004
DOI: 10.1159/000078620
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Tumors in Children: A Clinicopathologic Study of a 10-Year Review in Southern Taiwan

Abstract: Purpose: To describe the clinical and histopathologic characteristics of eyelid tumors in children in southern Taiwan. Methods: Patients younger than 17 years old with histologically confirmed eyelid tumors treated at Chang Gung Memorial Hospital (Kaohsiung) during 1991–2000 were subjected to a retrospective analysis. Patients with inflammation, granulation, hordeolum, chalazion and orbital or conjunctival extension were excluded. Results: Totally, 78 patients (46 boys and 31 girls) with eyelid tumors were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…[6] Different studies reported various frequencies of benign tumours some of which are similar to our study. Hsu and Lin et al series reported epidermal cysts (23.1%) [9] to be the most common lesion and Kersten et al reported it as the 2 nd most common lesion in their cases series(22.2%). [14] Four separate studies from Tehran, China, Southern Taiwan and South Korea have reported that the most frequent benign tumors were nevus, papilloma, and cysts.…”
Section: Discussionmentioning
confidence: 93%
“…[6] Different studies reported various frequencies of benign tumours some of which are similar to our study. Hsu and Lin et al series reported epidermal cysts (23.1%) [9] to be the most common lesion and Kersten et al reported it as the 2 nd most common lesion in their cases series(22.2%). [14] Four separate studies from Tehran, China, Southern Taiwan and South Korea have reported that the most frequent benign tumors were nevus, papilloma, and cysts.…”
Section: Discussionmentioning
confidence: 93%
“…and Ni7 were papilloma. In the study by Hsu and Lin8 the most frequent type of benign tumors in patients was dermoid cysts. In a survey from Saudi Arabia, the most common benign mass was hidrocystoma followed by chalazion 9.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these disparities are interesting due to demographic differences. For instance, in Hsu and Lin's study8 that reported dermoid cysts as the most frequent tumor, only pediatric and adolescent patients below 17 years were investigated. Certain geographic and climate conditions can also influence the frequency of different type of eyelid masses, for example, the higher incidence of hidrocystoma in a Saudi study9 is attributed, by the author, to the warm climate and excessive activity of sudoriferous glands in the inhabitants of this region 9…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of chalazion is variable among the literature studies. [8][9][10][11] It generally ranges from 0.2% to 0.7%. In the United States, the exact prevalence is not well-known, but it is commonly encountered among school children and adults between the ages of 30 and 50 years.…”
Section: Incidence Of Chalazionmentioning
confidence: 99%